Economic Growth and the Distributive Shares - Findlay, Ronald (Review of Economic Studies, 1960)
Economic Growth and the Distributive Shares Get access Ronald Findlay Ronald Findlay Rangoon and Massachusetts Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 3, June 1960, Pages 167–178, https://doi.org/10.2307/2296078 Published: 01 June 1960